Cavitation and Bubble Dynamics: Fundamentals and Applications - (:unkn) unknown (My University, 2021)
Cavitation and Bubble Dynamics: Fundamentals and Applications examines the latest advances in the field of cavitation and multiphase flows, including associated effects such as material erosion and spray instabilities. This book tackles the challenges of cavitation hindrance in the industrial world, while also drawing on interdisciplinary research to inform academic audiences on the latest advances in the fundamentals. Contributions to the book come from a wide range of specialists in areas including fuel systems, hydropower, marine engineering, multiphase flows and computational fluid mechanics, allowing readers to discover novel interdisciplinary experimentation techniques and research results. This book will be an essential tool for industry professionals and researchers working on applications where cavitation hindrance affects reliability, noise, and vibrations.
Keywords: Cavitation; Phase Change; Multiphase flows; Thermodynamics